About a Third of Nursing Home Social Services Directors Have Earned a Social Work Degree and License. Issue 7 (3rd October 2021) - Bern-Klug, Mercedes; Smith, Kevin M.; Roberts, Amy Restorick; Kusmaul, Nancy; Gammonley, Denise; Hector, Paige; Simons, Kelsey; Galambos, Colleen; Bonifas, Robin P.; Herman, Chris; Downes, Deirdre; Munn, Jean C.; et al.
ABSTRACT: Nursing home (NH) residents have high psychosocial needs related to illness, disability, and changing life circumstances. The staff member with the most expertise in addressing psychosocial needs is the social worker. However, federal regulations indicate that only NHs with 120+ beds need hire a social services staff member and that a "qualified social worker" need not have a social work degree. Therefore, two-thirds of NHs are not required to employ a social services staff member and none are required to hire a degreed social worker. This is in stark contrast to NASW professional standards. Reporting findings from this nationally representative sample of 924 social services directors, we describe the NH social services workforce and document that most NHs do hire social services staff, although 42% of social services directors are not social work educated. 37% of NHs have a degreed and licensed social worker at the helm of social services. The odds of hiring a degreed and licensed social workers are higher for larger NHs, especially if not-for-profit and not part of a chain. NH residents deserve psychosocial care planned by staff with such expertise. Quality of psychosocial care impacts quality of life.